Odpowiedź :
[tex](sin \alpha - cos \alpha)^2=\frac{1}{5}\\\\sin^2\alpha-2ain\alpha cos\alpha+cos^2\alpha=\frac{1}{5}\\\\1-2sin\alpha cos\alpha=\frac{1}{5}\\\\-2sin\alpha cos\alpha=\frac{1}{5}-1\\\\-2sin\alpha cos\alpha=-\frac{4}{5}\ \ \ |:(-1)\\\\ 2sin\alpha cos\alpha=\frac{4}{5}[/tex]
[tex](sin\alpha+cos\alpha)^2=sin^2\alpha+2sin\alpha cos\alpha+cos^2\alpha=1+2sin\alpha cos\alpha=1+\frac{4}{5}=1\frac{4}{5}=\frac{9}{5}[/tex]
Odpowiedź:
Szczegółowe wyjaśnienie:
(sinα-cosα)²=1/5
sin²α-2sinαcosα+cos²α=1/5
1-2sinαcosα=1/5
-2sinαcosα=1/5 -1
-2sinαcosα=-4/5 /(-1)
2sinαcosα=4/5
L=(sinα+cosα)²=sin²+2sinαcosα+cos²α=1+2sinαcosα=1+ 4/5=9/5=P
korzystamy z jedynki trygonometrycznej
sin²α+cos²α=1
i wzoru
(a+b)²=a²+2ab+b²